The Impact of Mudharabah Sukuk and Foreign Exchange on the Profitability of Islamic Commercial Banks in Indonesia - Safarida, Nanda; Muhammad, Alfian; Fahriansah; Sabda, Aulya (FEBI IAIN Langsa, 2023)
This study aims to determine the effect of Sukuk Mudharabah and Foreign Exchange on the profitability of Islamic commercial banks in Indonesia from 2014 to 2021. The data analysis technique used is panel data regression with the assistance of Econometric Views (Eviews). The results of the study indicate that Sukuk Mudharabah has a negative and insignificant effect on profitability (sig value. 0.413 > 0.05). Foreign exchange has a positive and significant effect on profitability (sig value. 0.024 <0.05). Additionally, sukuk mudharabah and foreign exchange both have a positive and significant effect on the profitability of Islamic Commercial Banks in Indonesia (sig value. 0.00 <0.05). These results demonstrate the impact of foreign exchange on Islamic Commercial Banks in Indonesia.